A Study of Gender Differences in Treatment of Critically Ill Newborns in NICU Of Krishna Hospital, Karad, Maharashtra - Kshirsagar, Vinayak Y; Ahmed, Minhajuddin; Colaco, Sylvia M (National Journal of Community Medicine, 2013)
Introduction: Sex ratio in India is adverse for girl. Gender-based health disparities are prevalent in India but very little data are available on care-seeking patterns for newborns. An attempt had been made to study gender differences in treatment of critically ill newborns in tertiary hospital. Methods: Study includes total deliveries, NICU admissions and patients leaving against medical advice in NICU and neonates who were not admitted in spite of need for NICU admission. A study of various socio-demographic parameters and its correlation to denial of health care were also studied. Result: A total of 191 babies were taken against medical advice, 134 (70.15%) females and 57 (29.84%) males. 141 babies in the NICU of which 94 (65.27%) were girls and 50 (34.72%) were boys. Families of 47 babies who needed NICU admission refused of which 40 (85.10%) were girls and 7 (14.89%) were boys. The odds ratio calculated is 3.448 which signify that chances of health care denial are 3.448 times greater for a female child. Various socio-demographic parameters were studied and significance of each parameter was determined. Conclusion: Factors like previous girl child, literacy of mother and socioeconomic status play an important role in seeking health care facilities.